Management of mandibular condylar fractures by the retromandibular approach – An evaluation of its complications - Shanmugam, Devakumari; Dominic, Neil; Thanasekaran, Vijhayapriya; Purushothaman, Amudha; Sridhar, Dinesh; Shanmugam, Devameena (Asian Journal of Medical Sciences, 2021)
Background: Mandibular condyle fractures are commonly encountered in the practice of maxillofacial surgeon. Even though being a commonly seen fracture, the fracture condyle of the mandible demands meticulous diagnosis and a tailor made treatment plan for each and every patient. The treatment plan largely depends on the age of the patient and the displacement of the fractured fragment. This retrospective study provides an insight in to the management of fracture mandibular condyle by retromandibular approach. Aims and Objectives: The aim of this study was to evaluate the complications of the retromandibular transparotid approach in surgically operated patients with mandibular condylar fractures. Materials and Methods: A retrospective study was performed by analyzing the treatment records of patients who underwent open reduction and internal fixation (ORIF) by the retromandibular transparotid approach for seven years. Thirty-five patients who fulfilled the criteria were included in the study. Clinical parameters such as marginal mandibular nerve weakness, sialocele, occlusal derangement and decreased mouth opening were recorded during the first, fourth and twelfth weeks postoperatively. The retrieved data were analyzed for complications of the retromandibular approach in the management of mandibular condylar fractures. Results: In patients (N= 35) who underwent ORIF by the retromandibular transparotid approach, findings recorded at the end of the first week included 5 patients with sialocele, 2 patients with derangement of occlusion, 6 patients with restricted mouth opening and 1 patient with marginal mandibular nerve weakness. However, postoperatively, at the end of 4 weeks, the only complication observed was sialocele in 3 patients. Furthermore, at the end of 12 weeks, sialocele had completely resolved in all 3 patients, and they were free of complications. Conclusion: The retromandibular transparotid approach is a reliable and straightforward technique with manageable complications.